2021
DOI: 10.7150/jca.58158
|View full text |Cite
|
Sign up to set email alerts
|

MTFR2, A Potential Biomarker for Prognosis and Immune Infiltrates, Promotes Progression of Gastric Cancer Based on Bioinformatics Analysis and Experiments

Abstract: Background: Mitochondrial fission regulator 2 (MTFR2) which can promote mitochondrial fission, has recently been reported to be involved in tumorigenesis. However, little is known about its expression levels and function in gastric cancer (GC). This study aims to clarify the role of MTFR2 in GC. Methods:We firstly determined the expression level and prognostic value of MTFR2 in GC by integrated bioinformatics (Oncomine, GEPIA, Kaplan-Meier Plotter database) and experimental approaches (RT-qPCR, western blot, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The disruption of this balance may contribute to the occurrence of different diseases, including different types of cancers ( Lin and Beal, 2006 ; Guo et al, 2020 ). Recent studies have indicated that dysfunctional mitochondrial fission is involved in the progression of some malignancies, including glioblastoma, liver cancer and gastric cancer ( Hernandez-Alvarez and Zorzano, 2021 ; Lenzi et al, 2021 ; Zhu et al, 2021 ). Furthermore, some studies have indicated that mitochondrial dynamics have an imperative function in the chemoresistance of cancer cells ( Kong et al, 2015 ; Cai et al, 2016 ; Huang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The disruption of this balance may contribute to the occurrence of different diseases, including different types of cancers ( Lin and Beal, 2006 ; Guo et al, 2020 ). Recent studies have indicated that dysfunctional mitochondrial fission is involved in the progression of some malignancies, including glioblastoma, liver cancer and gastric cancer ( Hernandez-Alvarez and Zorzano, 2021 ; Lenzi et al, 2021 ; Zhu et al, 2021 ). Furthermore, some studies have indicated that mitochondrial dynamics have an imperative function in the chemoresistance of cancer cells ( Kong et al, 2015 ; Cai et al, 2016 ; Huang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Proteins often need to dock several tertiary structures to each other to form quaternary structures for biological functions and metabolic reactions [ 21 ]. To investigate the potential mechanisms of protein physical interactions, we first selected RP2 to construct a network of proteins with which it can interact ( Supplementary Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…With the development of molecular biology and clinical treatment with precision therapy, researchers have been exploring new prognostic markers of GC at the molecular level. Zhu et al [3] revealed the expression, prognostic value, potential functional networks, protein interactions, and immune infltration of MTFR2 (mitochondrial fssion regulator 2) in GC, concluding that MTFR2 may be a potential prognostic marker and therapeutic target for GC patients. Zhu et al [34] explored the association between VEGFR-2 and the prognosis of GC.…”
Section: Discussionmentioning
confidence: 99%
“…GC is the ffth most common malignancy worldwide and the third leading cause of global cancer-related mortality [1,2]. Although clinical and surgical conditions improved significantly, the 5-year survival rate for GC patients remains very low, as more than 80% of patients are diagnosed at an advanced stage [3,4]. Now, surgical resection is still the most efective treatment for early GC.…”
Section: Introductionmentioning
confidence: 99%